An Evaluation of Successful Reclamation of Bauxite Residue through Afforestation Activities in South India - Chauhan, Suresh; Silori, C. S. (Indian Forester, 2012)
The present article is based on the results of a pilot project conducted to improve the physico chemical characteristics of bauxite residue (red mud) to make it suitable for rehabilitation through afforestation activities. Of the five tree species selected during nursery trials, Prosopis juliflora, Acacia nilotica, and Pongamia pinnata responded well in combination with 55% Redmud + 25% FYM + 15% Gypsum + 5% Vegetative dry dust + Bacteria + Mycorrihzae, while other two species, Melia azedarach and Acacia tortilis did not survive and thus were replaced by Albizia lebbek and Leucaena leucocephala during pilot implementation in 1.08 ha research plot of red mud of Hindustan Aluminium Company Limited (HINDALCO) at Belgaum, Karnataka, South India. Among the grass and legume species, all the selected four species viz. Brachiaria mutica, Brachiaria decumbens, Stylosanthes scabra and Sesbania sesban performed well. Continuous monitoring on growth pattern of tree and grass species and soil characteristics revealed remarkable changes in the physico chemical properties of red mud.